Prinsip Kepastian Hukum Pemberhentian Sementara Notaris yang Dinyatakan Pailit - Balqis Nurdiniasari Afrihasa; Muhammad Khoidin; Ainul Azizah (Syntax Idea)
The problems and research objectives taken include reviewing and analyzing the legal ratio of arrangements for notaries as public officials to be bankrupt, reviewing and analyzing temporary dismissals of notaries in accordance with the principle of legal certainty and reviewing and analyzing future arrangements for temporary dismissals as a result of being declared bankrupt. The research method used is legal research. The problem approach used in this research is the statute approach, conceptual approach and comparative approach. The sources of legal materials used are primary, secondary and non-legal legal materials. The results of the study conclude first, that notaries are public officials who are given directly by the state. Has special features that are different from other public officials. The position given by a Notary by issuing a legal product in the form of an authentic deed in providing services to the community. So that all legal products issued by a Notary have binding legal consequences because they can be used as evidence. Notaries are required to provide good services and good behavior. Notaries who have problems, such as being sentenced to temporary dismissal to dishonorable dismissal due to tripping over a bankruptcy case. This will affect the authentic deed he made. Second, the temporary dismissal of notaries involved in bankruptcy as stipulated in UUJN does not provide legal certainty and is considered vague. When referring to the Bankruptcy Law and PKPU, temporary dismissal sanctions cannot be applied because the bankrupt object is deemed not in accordance with this law, and notaries who are bankrupt under this law are not included in the legal subject matter of the Bankruptcy Law and PKUPU. Third, future arrangements regarding the temporary dismissal of a Notary due to being declared bankrupt have occurred disharmony in the application of the Bankruptcy Law and PKPU regulated in the UUJN. UUJN should pay attention to one of the principles applied in the Bankruptcy Law and PKPU, namely the principle of business continuity.